Effect of Microneedle Geometry and Supporting Substrate on Microneedle Array Penetration into Skin. Issue 11 (11th September 2013) - Kochhar, Jaspreet Singh; Quek, Ten Cheer; Soon, Wei Jun; Choi, Jaewoong; Zou, Shui; Kang, Lifeng
<x xml:space="preserve">Abstract</x> Microneedles are being fast recognized as a useful alternative to injections in delivering drugs, vaccines, and cosmetics transdermally. Owing to skin's inherent elastic properties, microneedles require an optimal geometry for skin penetration. In vitro studies, using rat skin to characterize microneedle penetration in vivo, require substrates with suitable mechanical properties to mimic human skin's subcutaneous tissues. We tested the effect of these two parameters on microneedle penetration. Geometry in terms of center‐to‐center spacing of needles was investigated for its effect on skin penetration, when placed on substrates of different hardness. Both hard (clay) and soft (polydimethylsiloxane, PDMS) substrates underneath rat skin and full‐thickness pig skin were used as animal models and human skins were used as references. It was observed that there was an increase in percentage penetration with an increase in needle spacing. Microneedle penetration with PDMS as a support under stretched rat skin correlated better with that on full‐thickness human skin, while penetration observed was higher when clay was used as a substrate. We showed optimal geometries for efficient penetration together with recommendation for a substrate that could better mimic the mechanical properties of human subcutaneous tissues, when using microneedles fabricated from poly(ethylene glycol)‐based materials. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:4100–4108, 2013